The effectiveness of emotional rational behavior therapy on body image, body mass index and reducing social anxiety in overweight adolescents - Habibi Zanjani, Nazanin; Barazian, Saeideh; Ahadi, Hassan (Applied Family Therapy Journal (AFTJ), 2022)
Aim: To determine the effectiveness of emotional rational behavior therapy on body image, body mass index and reduce social anxiety in overweight adolescents. Methods: The present research method was quasi-experimental with pre-test and post-test design and follow-up with a control group. The statistical population of this study consisted of adolescent girls and boys who had referred to clinics in Tehran in 2019 with the problem of overweight and obesity, from which 40 people were selected as a sample by available sampling method. After selecting individuals, they were randomly assigned to two experimental groups and one control group (20 people in each group). The experimental group intervention was group therapy based on emotional rational behavioral therapy (Ellis and Dryden, 1997) and consisted of eight sessions lasting 120 minutes. Data were analyzed using Littleton et al.’s (2005) Body Image Concern Questionnaire, Connor et al.’s (2000) Social Anxiety Inventory, and repeated measures analysis of variance using SPSS.22 software. Data were analyzed by repeated measures analysis of variance and SPSS.22 software. Significance level in this study was considered 0.05. Results: The results showed that rational-emotional behavior therapy in body image (F=25.29, P<0.001), body mass index (F=3.59, P=0.036), and reduction of anxiety Social (F=5.49, P=0.026) Adolescents were effective overweight (P<0.001). Conclusion: Based on the research findings, it can be said that rational-emotional behavior therapy can have positive effects on body image, body mass index and reduce adolescent social anxiety.